Analysis of the efficiency of structural and technological solutions in the production of component units of lattice furniture products - Grytsak, S.A.; Gayda, S.V.; Kushpit, A.S.; Salapak, L.V. (Forestry, Forest, Paper and Woodworking Industry, 2023)
The existing types of backs of carpentry chairs, which are part of a kitchen set of furniture, which are constructed from elements of hard wood species, in particular oak, and the technological processes of their manufacture have been analyzed. The technologies and production processes accompanying the creation of the backs of carpentry chairs are analyzed and described in detail. The methodology of research and comparison of technological processes of manufacturing the backs of carpentry chairs with structural features are substantiated. The necessary materials for two types of manufacturing backs of carpentry chairs from oak wood from natural wood were selected and calculated. The necessary basic equipment was selected and calculated according to the developed manufacturing technologies for two options for the manufacture of chair backs. The necessary technological routes for each variant of manufacturing the backs of carpentry chairs were selected, developed and calculated. Two shop plans are proposed according to the developed technologies for manufacturing the backs of carpentry chairs. A comparison of the amount of equipment loading of each variant of manufacturing the backs of carpentry chairs was carried out. The results of the preliminary analysis based on the data of three indicators (cost and capacity of the equipment, number of employees) gave the right to recommend the second option for the manufacture of the backs of carpentry chairs, which are included in the set of kitchen furniture, which is constructed from prepared elements of solid species of wood, in particular oak from natural wood, where the cost of equipment is the lowest and amounts to UAH 827.65 thousand, the number of employees is 8, the total power is 15.27 kW. On the other hand, the cost of materials for the first option is much higher than in the second. Economic calculations proved and calculated that the least expensive for the implementation of the annual program in the amount of 30,000 backs of carpentry chairs, which are included in the set of kitchen furniture, which is constructed from prepared elements from hard species of wood, in particular, oak from natural wood, is the second option, where the investments amounted to UAH 14,252.98 thousand, which is 20% less than in the first option.